Post-Handover Quality Management Index of Electric Housing Work - Junmo Park; Deokseok Seo (Advances in Civil Engineering)
Since housing electrical work is essential in the aspect of electricity use and electrical accidents, it is necessary to properly design, construct, and manage it to avoid quality problems. However, disputes are intensifying in Korea due to numerous quality problems after the house is handed over to the owner. Although related standards have been established and some studies have been conducted, there is a lack of discussion on housing electrical work because the housing quality problem is varied. In this study, the cases of quality problems that occurred in housing electrical works were investigated, while 52 quality control indices were presented and classified according to detailed work category, object, and problematic occurrences. In addition, the number of cases of quality problems for each quality management index and the repair cost ratio were used as a scale to understand the status of quality management. Finally, 11 quality indices were suggested as candidates of important indices which needed to be controlled to focus on the housing electrical work by comparing the above 52 indices. The comparison was made on which one was best suited to the Pareto principle, a quality management strategy, among the candidates for the critical index and the indices suggested by relevant standards and previous studies. The comparison results showed that the candidates of the essential indices suggested in this study conformed to the Pareto principle, while other indices hardly conformed to it. Therefore, if the quality control strategy of choice and concentration for housing electrical works is used, focusing on these vital index candidates can effectively assist in handling the occurrence of quality problems.